The philosophy of the Sunni rooting of history (Muhammad Baqir al-Sadr as a model) (Journal of Imam Al-Kadhim College, 2023)
Abstract:                                                                                            This paper studies the human need to know the rules  that govern the movement of history in its formation and  orientation,and  follow those rules in the Qur’anic content, and reveal their methods, characteristics, forms and differentiate between the field of rules in the historical  context, and assimilate them to be present and make use of   them in the future                                                                                                   Muhammad Baqir Al-Sadr reveals those rules to have an original content corresponding to Western thought in all its philosophical schools of history and rooting rules history and  Positive, humanitarian , idealistic realistic proposals which have one-element  centered around the centrality of the mind or the source of the sky and its direct connection, which in Al-Sadr’s view were limited proposals in the rationing of history and, its philosophy and Forecasting the future Therefore, al-Sadr presented his approach, in which he relied on two elements: divine and human under the name (Mintaqat al-faragh which is the general integrated framework for al-Sadr’s  theory in the cosmic rules with social, economic, jurisprudential and historical conten .Thus, Al-Sadar open a new, cognitive, academic, research and an integrated school in the field of Philosophy of history.
Keywords: philosophy of history - Sunnah rooting - laws of history - philosophy of waiting